À sombra do rei: elementos críticos para a análise da discografia de Roberto Carlos (1961-1982) - Faraco, Felipe Berger (2012)
It is a study that deals with part of the artistic production of Roberto Carlos. The singer is the biggest phenomenon of Brazilian popular music, totaling over 120 million albums sold (SANCHES, 2009). Moreover, his personal history followed the formation and organization of national cultural industry. Consequently, to understand this properly, we must inevitably follow the trajectory of this artist. To qualify the characteristics involved in the process, we analyzed the discography of Roberto Carlos launched in the range of 1961 to the year of 1982 a total of 22 albums. This period includes the first recordings of the singer, to the apex of his carrer. The parameters contained in the selected material have information relevant to the study of the musician s work with regard to its insertion in the panorama of production within capitalist logic. The research is guided by three core elements represented sonically, through the musical material; by semantics, reflected in the content of the lyrics; and visually, using the covers of his albums. In this sense, we proceed according to the thesis of Theodor Adorno, in which the musical parameters in themselves are indicators of how the logic of the commodity affects artistic production. Standardization is its most striking reflection. We conclude that the work of Roberto Carlos is composed of a series of standards of production. To that extent, all the material conforms, to some degree, the purpose of developing a business asset. It is a fact that permeates the entire studied material. However, there are differences given by the transition from an initial period of instability that was later replaced by a more sophisticated formulations of production.